Empowerment of Islamic Boarding Schools Through Entrepreneur Development of Fish Cultivation - Shofi Mulyati, Dewi; ., Nugraha; Febri Suahati, Ajrina (KnE Social Sciences, 2023)
Entrepreneurship is a field that is growing rapidly, in line with the development of the business world. One important aspect that can encourage the development of entrepreneurship is the education sector. Islamic boarding schools, as Islamic educational institutions in various provinces in Indonesia, can be used as incubators and for business development purposes. Entrepreneurship is expected to increase the empowerment of Islamic boarding schools for the benefit of the people. Islamic boarding schools are expected to improve the economy that will prosper all students, teachers, and the entire academic community and the area around the boarding school. This research aimed to identify the potential of Islamic boarding schools (nature potential and human potential). One way to develop entrepreneurship is through mentoring and counseling on entrepreneurship in freshwater fish farming. Mentoring and counseling involving the Garut Regency Fisheries and Animal Husbandry Service as a form of sustainable government support for entrepreneurship development programs at Islamic boarding schools. Keywords: Islamic boarding school, entrepreneurship, fish cultivation